Analysis of Stunting Incidence Based on Knowledge, Maternal Characteristics, and Nutritional Status - Chairiyah, Royani; D P, Puspitasari Nurul; Susanti, Susanti; Inayati, Rohmanatul (Sarana Ilmu Indonesia (salnesia), 2024)
One of the issues impeding human development worldwide is stunting. This study's goal is to examine the prevalence of stunting according to characteristics, knowledge, and nutritional status in Kebayoran District, South Jakarta. This kind of study uses a cross-sectional research design and is quantitative in nature. This research was conducted in Kebayoran Baru District, South Jakarta, during November-December 2021. All mothers with toddlers made up the study's subjects, with a sample of 50 subjects participating in the Family Hope Program (PKH) with purposive sampling techniques. Data collection method using questionnaires. Logistic regression and the Chi-square test are the statistical tests that are employed. The results showed maternal knowledge with a p-value of 0,044, age (p-value = 0,031), educational attainment (p-value = 0,012), marital status (p-value = 0,837), economic status (p-value = 0,000), and nutritional status (p-value = 0,000). In conclusion, a relationship exists between knowledge, characteristics (age, mother's education level, mother's working status, economic status), and nutritional status in relation to stunting. Additionally, there is no connection between the prevalence of stunting and marital status. Education, economic status, and nutritional status are the primary determinants of stunting incidence in Kebayoran Baru, South Jakarta.